Persepsi dan Respons Mahasiswa terhadap Berita Hoax dan Ujaran Kebencian: Tinjauan Berdasarkan Qaulan Sadidan dan Qaulan Balighan - Syahril Furqany; Abdullah Abdullah (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2024)
This research examines students' perceptions and responses to hoax news and hate speech. With the development of technology and social media today, the opportunity to spread hoax news is getting bigger. People who lack digital literacy will be very easily exposed to fake news. The research method used a quantitative method by conducting a survey of 40 students of the Islamic Communication and Broadcasting Study Program, Faculty of Da'wah and Communication, UIN Ar-Raniry. The research results show that students very often encounter fake news or hoaxes on social media, but sometimes they don't know how to differentiate between them. The most news about hoaxes is political news. While hate speech is very often experienced by students, students believe that hate speech can create divisions between individuals. The step they took was to report several cases of hate speech. Cases of hoax news and hate speech can be resolved by understanding more deeply the principles of Islamic communication, namely Qaulan Sadidan and Qaulan Balighan. Of course, there is a need for digital da'wah in strengthening the principles of Islamic communication.